The Use of Dornase Alfa in the Management of COVID-19-Associated Adult Respiratory Distress Syndrome - Andrew Toma; Christina Darwish; Michele Taylor; Justin Harlacher; Ribal Darwish (Critical Care Research and Practice)
Objective. Currently, management of acute respiratory distress syndrome (ARDS) in COVID-19 infection with invasive mechanical ventilation results in poor prognosis and high mortality rates. Interventions to reduce ventilatory requirements or preclude their needs should be evaluated in order to improve survival rates in critically ill patients. Formation of neutrophil extracellular traps (NETs) during the innate immune response could be a contributing factor to the pulmonary pathology. This study suggests the use of dornase alfa, a recombinant DNAse I that lyses NETs, to reduce ventilatory requirements and improve oxygenation status, as well as outcomes in critically ill patients with ARDS subsequent to confirmed or highly suspected COVID-19 infection. Design. A single-institution cohort study. Setting. Intensive care unit in a tertiary medical center. Patients. Adult patients with acute respiratory distress syndrome (ARDS) admitted to the ICU with confirmed COVID-19 infection. Intervention. Treatment with aerosolized dornase alfa. Measurements and Main Results. Of 39 patients evaluated, most patients had improvement in oxygenation measured by increase in the PaO2/FiO2 ratio, reduction in ventilatory support or other supportive oxygen requirements, and partial resolution of bilateral opacities visible on CXR, as well as improved outcome. Conclusions. Administration of inhalational dornase alfa via a filtered nebulizer medication system or through an adapter in a ventilator circuit should be considered in all COVID-19-positive patients with ARDS as early in the disease course as possible.